Evaluasi Kurikulum Merdeka Tahun 2024 Mata Pelajaran Pendidikan Agama - Mahfud; Nurfuadi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to determine the 2024 independent curriculum program for PAI subjects at SMK Mulia Bakti Purwokerto. This research examines the program, implementation and impact of the independent curriculum on PAI subjects. This research is descriptive research with a qualitative approach with a case study design. This research carries out observations, interviews and documentation so that it can describe the research object without affecting the situation and as it is. The results of this research show the obstacles faced by schools both in terms of teacher components, infrastructure, supporting resources and of course students. However, this can be anticipated with solutions such as following training, equalizing paradigms and being consistent. In implementing the independent curriculum in PAI lessons, there are not too many changes from the previous curriculum. Student activities are the main thing or student-centered learning (student center). The sustainability of the implementation of the independent curriculum must be adjusted to the ability and consistency in its implementation. Of course, there are various obstacles and evaluation can be used as a solution in implementing the independent curriculum. As we know, the independent curriculum is a refinement of the previous curriculum. However, what makes this independent curriculum different is that there are different projects in each subject, making learning more fun and varied.